LIMBAH TEMPURUNG KELAPA SEBAGAI ALTERNATIF PENYERAP LOGAM BERAT YANG RAMAH LINGKUNGAN DAN EKONOMIS - Mycelia Paradise; Edi nursanto; Nurkhamim (Retii, 2020)
Coconut shell is one of the waste that has not been used optimally and its availability is abundant. Usually coconut shell used as handicrafts. Several studies shown that coconut shell can be used as activated carbon to adsorb heavy metals from wastewater through the adsorption process. Charcoal made from coconut shell are then activated using heating (physical activation) and using chemical solutions as activators (chemical activation). Chemical solutions usually used as activators are acidic or alkaline solutions such as hydrochloric acid (HCl), sulfuric acid (H2SO4), zinc chloride (ZnCl2), sodium carbonate (Na2CO3), sodium chloride (NaCl), phosphoric acid (H3PO4), and sodium hydroxide (NaOH). Several studies shown that coconut shell activated carbon is able to adsorb heavy metals copper (Cu), iron (Fe), zinc (Zn), lead (Pb), cadmium (Cd), chromium (Cr), and aluminum (Al) with good adsorption capacity Keywords: adsorption, coconut shell activated carbon